2018
DOI: 10.1371/journal.pone.0195390
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Mycobacterium simiae: A retrospective study from a tertiary care center in Lebanon

Abstract: ObjectiveThe objective of this study is to describe the clinical significance of Mycobacterium simiae at a major tertiary care center in Lebanon.MethodsThis is a retrospective study of patients with positive cultures for M. simiae isolated between 2004 and 2016 at the American University of Beirut Medical Center.ResultsThis study included 103 M. simiae isolates recovered from 51 patients. Their mean age was 62.7 years. The majority were males and smokers. Specimens were mostly from respiratory sources (97%). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…We hypothesize that the high rate of M. simiae in Iran, may be due to the contamination of water supplies with this pathogen, a finding that was previously reported in studies conducted in Iran [18,19]. Temperature and humidity have also been reported to be associated with NTM infections [16,20]. Another explanatory factor may be the presence of underlying diseases among patients with M. simiae as described by Coolen-Allou…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We hypothesize that the high rate of M. simiae in Iran, may be due to the contamination of water supplies with this pathogen, a finding that was previously reported in studies conducted in Iran [18,19]. Temperature and humidity have also been reported to be associated with NTM infections [16,20]. Another explanatory factor may be the presence of underlying diseases among patients with M. simiae as described by Coolen-Allou…”
Section: Discussionmentioning
confidence: 64%
“…Van Ingen et al in the Netherlands, showed resistant rates of 86% to amikacin, 77% to ciprofloxacin, 36% to moxifloxacin and 9% to clarithromycin in clinical isolates of M. simiae [7]. M. simiae isolates from Hamieh et al, study in the Lebanon were mostly susceptible to amikacin and clarithromycin and less susceptible to moxifloxacin and ciprofloxacin [16]. Likewise…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This species has been associated with humid weather and water niches, as reported for Cuba, Arizona, Texas, Iran, Gaza and Israel [13]. The humid weather in Lebanon, a Mediterranean costal country, may also explain the high prevalence of M. simiae in this area of the world [13,14]. Few other countries in the Middle East and the Gulf region reported on the recovery of this species, albeit with lower rates such as Oman (8%) and Turkey (2.1%) [8].…”
Section: Discussionmentioning
confidence: 84%
“…In Lebanon, a couple of published articles addressed NTM, mostly as case reports [9][10][11][12][13][14] but none has comprehensively revealed the present species nor their antimicrobial resistance (AMR) profiles. Besides, the recovery of NTMs has been increasing, with rates reaching 55 to 67% among isolated mycobacteria, as noted for instance in our medical center over the last five years.…”
Section: Introductionmentioning
confidence: 99%